Involvement of the ovarian-specific Mro-IR in oogonia differentiation and oocyte development in freshwater giant prawn Macrobrachium rosenbergii - Ma, Wen-Ming; Xu, Hai-Jing (Frontiers in Endocrinology, 2025)
IntroductionMro-IR is an insulin-like receptor and is uniquely expressed in the ovary of the freshwater giant prawn Macrobrachium rosenbergii. However, the understanding of this conserved receptor involved in the molecular mechanism underpinning ovarian development and female reproduction of M. rosenbergii is still fragmentary.MethodsIn the present study, in vivo knockdown of Mro-IR in the proliferative stage and premature stage of ovarian development in female prawn induced abnormal oogonia differentiation and disordered oocyte development.ResultsThe histological analysis showed that Mro-IR-silencing caused abnormal cellular morphology of some early vitellogenic oocytes (Oc2) and significantly delayed the proliferation of late vitellogenic oocytes (Oc3) in the proliferative stage of the ovary. Meanwhile, the Mro-IR silence led to the abnormal Oc3 with indistinct boundary and destructive structure of yolk accumulation in Oc3 in the premature stage of the ovary. Furthermore, to expound the potential roles of Mro-IR in ovarian development, a large amount of new data on significantly differentially upregulated and downregulated transcriptions was enriched, and the response of the primary Kyoto Encyclopedia of Genes and Genomes (KEGG) biological pathways was investigated. Their possible molecular regulatory relationships in gonad development and reproduction were briefly illustrated in the putative intuitive cascade regulation axis or networks.DiscussionThis finding offered new insight regarding the mechanism of the IR gene family in ovarian development and reproduction of crustaceans.